2016
DOI: 10.1186/s13643-016-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

How lay health workers tailor in effective health behaviour change interventions: a protocol for a systematic review

Abstract: BackgroundLay health workers (LHWs) are utilised as a channel of delivery in many health interventions. While they have no formal professional training related to their role, they utilise their connections with the target group or community in order to reach individuals who would not normally readily engage with health services. Lay health worker programmes are often based on psychological theories of behaviour change that point to ‘tailoring to individuals’ needs or characteristics’ as key to success. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…While it should not be assumed that knowledge and beliefs about HIV and ART are not retained from previous counseling sessions, HIV knowledge in patients is limited in some areas, despite previous counseling. Gauging patient knowledge at counseling onset in order to customize the counseling and education message, may be one way of tailoring the counseling education messages (Hawkins, Kreuter, Resnicow, Fishbein, & Dijkstra, 2008; Hodgins et al, 2016), ensuring that education and counseling is effective at different stages of treatment for each patient (Nozaki et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it should not be assumed that knowledge and beliefs about HIV and ART are not retained from previous counseling sessions, HIV knowledge in patients is limited in some areas, despite previous counseling. Gauging patient knowledge at counseling onset in order to customize the counseling and education message, may be one way of tailoring the counseling education messages (Hawkins, Kreuter, Resnicow, Fishbein, & Dijkstra, 2008; Hodgins et al, 2016), ensuring that education and counseling is effective at different stages of treatment for each patient (Nozaki et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…With the increasing numbers of individuals enrolling into therapy, some of whom may have previously received counseling, it may be useful to know whether knowledge and beliefs about HIV and ART are retained from previous counseling. This could help to tailor counseling sessions to individual patient needs by customizing the education messages and biomedical content, as well as to inform the number and duration of readiness sessions required to reduce the human resource burden (Hodgins, Gnich, Ross, Sherriff, & Worlledge-Andrew, 2016; Nozaki et al, 2013). Individuals who retain high levels of information from previous counseling could potentially be started on ART more rapidly.…”
mentioning
confidence: 99%
“…The LHA-guided health interventions are also in accordance with several psychological theories targeting behavioural changes that focus on specific needs and consider specific characteristics of a targeted audience as a key to success. 14 In the current study, we compared two types of oral self-care related outcomes between the two study groups at two different observation periods. Examination of OSC-P (outcome 1) allowed us to evaluate the overall quality of a child's oral hygiene, while the assessment of OSC-S (outcome 2) helped us to evaluate the skills necessary for performing proper oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…13 Previous research has shown that school-based peer-led education delivered by teachers was as effective as the health education provided by dental professionals. 13,14 We believe that children can also be educated as LHAs to become peer leaders and by attributing them such roles we can also expect their empowerment. Placing children in a leadership role when they are young can increase their selfesteem, self-efficacy, and self-empowerment; therefore, improving not only their own dental behaviours but also their feeling of wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…70 The CASP's criteria (aims, methodology, design, recruitment strategy, data collection, researcher/sample relationship, ethical issues, data analysis, statement of findings, value of research) allow the derivation of an overall assessment of a study's quality as strong, moderate or weak. 71 Evaluations were graded as weak if they did not meet both of the first two criteria, and as moderate or strong based on the remaining eight criteria. For both EPHPP and CASP, after independent ratings, reviewers discussed ratings with discrepancies and reached consensus.…”
Section: Study Qualitymentioning
confidence: 99%